(untitled) (REMUNOM, 2025)
Odontogenic keratocyst (OK) is a developmental odontogenic cyst that is mostly asymptomatic, slow-growing, infiltrative to adjacent tissues, and has a high recurrence rate. Therefore, this study aims to report a clinical case of a 2-year follow-up of an odontogenic keratocyst. A 32-year-old male patient was referred to the Oral and Maxillofacial Surgery and Traumatology Service of the School of Dentistry of the Federal University of Mato Grosso do Sul after a radiographic finding of a radiolucent lesion associated with impacted tooth 38. The patient reported no comorbidities or complaints related to the lesion. Physical examination revealed no noteworthy changes. Panoramic radiographs revealed a radiolucent lesion measuring approximately 2 cm in its largest extent, affecting the angle and body of the left mandible, associated with teeth 36, 37, and 38, the latter being impacted horizontally. After analysis, it was decided to perform excision of tooth 38, combined with cystic decompression and placement of a rubber device to reduce the cystic cavity, allowing its definitive enucleation later without compromising the integrity of the mandible. The diagnostic hypotheses were odontogenic keratocyst, ameloblastoma, and central giant cell granuloma. Histopathological examination confirmed the diagnosis of an odontogenic keratocyst. On postoperative day 21, the decompression device was removed, and the treated region was monitored by imaging for 2 years. After a 6-month period, with tomographic regression of the lesion, the patient underwent total enucleation of the cystic remnant. Subsequently, curettage of the lesion was performed to stimulate bone formation and remove residual epithelial islands. Therefore, it can be inferred that initial conservative treatment, with decompression of the lesion and subsequent enucleation, despite presenting the possibility of recurrence of the OC, is adequate to prevent mandibular weakening or fracture and also minimize the possibility of inferior alveolar nerve paresthesia. The patient remains under follow-up, and the treatment has yielded satisfactory results to date.